I Can Read it all by Myself : Bright and Early Books : Great Day for Up - Seuss, Dr. Dr.; Blake, Quentin (New York Beginner Books, 1974)
Rhymed text and illustrations introduce the many meanings of "up."
Keywords: Up (The word) -- Fiction; Stories in rhyme; Humorous Stories; Up (The word) -- Juvenile fiction; Stories in rhyme; Humorous Stories; Early readers